PERBAIKAN KUALITAS CITRA DENGAN FUSION UNSUR LUMINANCE, CHROMATIC DAN SALIENCY - Jaya, Liani; Lina, Lina (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Digital image processing is a branch of informatics engineering. Image processing is an attempt to transform an image or image into another image using certain techniques. The purpose of this application is to improve the quality of the image. The use of test images and imagery training, for image training using the images not in the water, and the image of Laplacian, while the test images using the image of double Laplacian and white balance with the parameter 0.5, 0.8, 1.0 and 1.2. The design is made in the form of software applications to improve the quality of the image fusion method. For data input will use the White Balance and Laplacian filter as a comparison with the original image taken. Then they will release the data output using the Weight Map that in a Luminance Weight Map, Chromatic Weight Map and Saliency Weight Map. In this resarch, applications using Visual Basic.Net 2015.